Jamovi-Assisted Ethnomathematics Learning for Data Analysis: A Community Service Initiative with the Mathematics MGMP in South Sumatera - Nila Kesumawati; Yunika Lestaria Ningsih; Lusiana; Jumroh; Rohana; Eka Fitri Puspa Sari; Allen Marga Retta (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: Mathematics learning is frequently perceived as abstract and disconnected from students’ daily experiences. Ethnomathematics offers a culturally responsive approach by embedding mathematical concepts within community traditions. However, teachers often face challenges in analyzing classroom data due to limited familiarity with accessible statistical software. This community service program addressed the need to strengthen ethnomathematics-based instruction supported by digital data analysis tools, particularly Jamovi. Purpose of the Study: This study aimed to enhance teachers’ understanding of ethnomathematics and improve their competence in applying the Jamovi application for statistical data analysis in mathematics learning. Methods: The program employed a participatory training model consisting of preparation, implementation, and evaluation stages. Activities included socialization sessions, seven online workshops, and one offline session involving 50 mathematics teachers from the MGMP forum. Pre-tests, post-tests, product presentations, and satisfaction questionnaires were used to evaluate outcomes. Data were analyzed using descriptive statistics and Normalized Gain (N-Gain). Results: The findings indicate high participant satisfaction, with an average of 70.6% selecting “Strongly Agree.” Teachers’ mean scores improved from 66.56 (pre-test) to 85.76 (post-test), with an average N-Gain of 0.59 (medium-to-high category). The results demonstrate that integrating ethnomathematics with Jamovi effectively enhances teachers’ statistical literacy, technological competence, and ability to design contextual mathematics learning.